Laminin-511 and recombinant vitronectin supplementation enables human pluripotent stem cell culture and differentiation on conventional tissue culture polystyrene surfaces in xeno-free conditions. Issue 41 (4th October 2021) - Liu, Ya-Chu; Ban, Lee-Kiat; Lee, Henry Hsin-Chung; Lee, Hsin-Ting; Chang, Yu-Tang; Lin, Yun-Ting; Su, Her-Young; Hsu, Shih-Tien; Higuchi, Akon
Abstract : Human pluripotent stem cells can be successfully cultured for long passages on uncoated tissue culture polystyrene (TCP) dishes in xeno-free medium supplemented with optimal ratio and concentration of laminin-511 and recombinant vitronectin. Abstract : Human pluripotent stem cells (hPSCs) are typically cultivated on extracellular matrix (ECM) protein-coated dishes in xeno-free culture conditions. We supplemented mixed ECM proteins (laminin-511 and recombinant vitronectin, rVT) in culture medium for hPSC culture on conventional polystyrene dishes. Three hPSC cell lines were successfully cultivated on uncoated polystyrene dishes in medium supplemented with optimal conditions of laminin-511 and rVT. Excellent colony shape and colony size as well as high expansion fold of hPSCs were found under these conditions, whereas the colony size was small and poor expansion fold was found solely on L-511-coated dishes. A small portion of L-511 in the culture medium supported hPSC adhesion and prevented the adhesion from being too strong on the uncoated dishes, and rVT in the culture medium further supported adhesion of hPSCs on the dishes by maintaining their pluripotency. Having the optimal composition of L-511 and rVT in the culture medium was important for generating good hPSC colony shapes and sizes as well as a high expansion fold. After long-term culture of hPSCs on uncoated dishes supplemented with the mixed proteins, the hPSCs successfully showed pluripotent markers and could differentiate into a specific lineage of cells, cardiomyocytes, with high efficiency.